Interplay of microRNAs to genetic, epigenetic, copy number variations of cervical cancer related genes. (November 2020) - Dai, Jingfang; Wang, Lu; Li, Li; Tian, Xiaona; Shang, Zhuqun; Li, Hongjuan
Highlights: More than Ten CNVs were significantly associated with early-onset Cervical cancer. The expression analysis showed that miR-182 was significantly upregulated in Cervical tumor compared to normal. The results showed that mitogen associated protein 3 kinase 3 ( MAP3K3) and FAM83H are direct targets of miR-182. Suggesting that miR-182 has oncogenic properties in Cervical cancer. Abstract: This study was to analyses the miRNAs role in cervical cancer and possibilities of microRNA-based markers as diagnostic tools. Genome wide analysis was performed for CNV detection using PennCNV and QuantiSNP. The associated mRNA qRT-PCR detection was used to measure quantities of microRNA gene expression. More than 10 CNV regions has a significant relationship with cervical cancer risk for both CNV detection algorithms. A total of 34 CNVs was detected by QuantiSNP while it was 27 in case of PennCNV, among which 22 CNVs was found to be overlapping between these two algorithms. the mRNA was analyzed for its expression on 36 carvical tumor normal tissue pairs of four targets i.e., MAP3K3, RIPK2, DIRAS3 and GAS7 . These infers that there was a significant downregulation of all the four genes cervical tumor. Our results showed that miR-182 can modulate the expression of FAM83H, DIRAS3, RIPK2 and MAP3K3 in cervical cancer. Therefore, indicated that miR-182 can acts through these signaling pathway in proliferation of cervical cancer cells. The expression of tumor modulator miRNAs can be controlled by miRNA replacement therapy. Several miRNAs have been used for this purpose. The modulation of various signaling pathway and proteins in cervical cancer cells by miR-182 needs further clarification.